Continuous change in spring-mass characteristics during a 400 m sprint - Hobara, H.; Inoue, K.; Gomi, K.; Sakamoto, M.; Muraoka, T.; Iso, S.; Kanosue, K. (Journal of Science and Medicine in Sport, 2010)
The purpose of the present study was to utilise a spring-mass model to continuously measure vertical stiffness (Kvert) and leg stiffness (Kleg) over an entire 400 m sprint, and investigate the relationship between leg spring stiffness (Kvert and Kvert) and the performance characteristics of mean forward running velocity (Vforwad), mean stride frequency (fstride), and mean stride length (Lstride). Eight well-trained male athletes performed a 400 m sprint with maximal effort on an outdoor field track. Kvert was calculated from the subjects` body mass, ground contact time and flight time at each step. Vforwad, fstride and Lstride were determined from video images. Kvert and Vforwad peaked at the 50-100 m interval, and consistently decreased from the middle to the later part of the sprint. Kleg peaked at first 50 m interval, and remained constant from next 50 m interval to finish. As compared with peak values, Kvert and Vforward in the last 50 m decreased by about 40% and 25%, respectively. A significant positive linear relationship existed between the Kvert and Vforward. While Kvert was significantly correlated with fstride, it had no correlation with Lstride. Further, no significant positive linear relationship was found between Kleg and Vforward, fstride, or Lstride. This result indicates that in order to keep Vforward at later stage of a 400 m sprint, maintaining the higher fstride through retaining a higher Kvert would be necessary.